Contaminación aeróbica orgánica en asociación de un mercado saludable en los centros de abastos Belén y Central. Iquitos, 2020 - Rodriguez Arbildo, Kevin (2022)
The study addresses attitudes about aerobic organic pollution as indicators of behavior regarding air pollution due to exposure to organic waste in public environments, and the perception of a healthy market as indicators of the way in which they appreciate and value the physical and social environment. urban planning with a sustainable city approach. With this purpose, the study was carried out in the Central markets (Iquitos district) and La Casona de Belen (Belen district) in the city of Iquitos. The approach was quantitative, correlational, the design of non-experimental, cross-sectional research. The population was determined based on the fixed sales stalls of the Belen (260 stalls) and Central (164 stalls) markets, with which the sample size of Belen (124 stalls) and Central (78 stalls) was calculated. The interview was used through a structured survey on attitude and perception; Analysis of variance and Spearman's r correlation test were performed to determine if there is a significant influence between the variables under study. The results report that the sellers have a high environmental attitude; related to the management of waste generated in the markets, and in this way reduce pollution and collaborate in improving the quality of the environment in the markets, while the perception is that of unhealthy markets and indifference, it is say they do not care if the markets are healthy or not. Finally, the hypothesis test (Spearman's Rho coefficient) showed that there is no significant relationship between the environmental attitude and the perception of a healthy market in the central markets and the Belen mansion, therefore the alternative hypothesis is rejected and accepts the null hypothesis proposed in this thesis.